DARI KONSUMERISME KE KONSUMTIVISME (Dalam Perpektif Sejarah Filsafat Barat) - Armawi, Armaidy (Jurnal Filsafat "WISDOM", 2007)
In this paper, the author tries to analyze of the consumptive behavior, especially the wasteful consumption of modern men and unfold of the intrinsic values and philosophical background of consumerism in the history of philosophy perspective (pre and modern western philosophy). He also tries to retrace the meaning movement of the consumerism to consumptivism (high mass consumption) and its social implication to the development of history of human civilization and their environment. The results are analysis on the comsumptive behavior describes the meaning of consumerism that has been changed from its positive sense, as a movement of consumer protection to its negative sense, as a wasteful consumption.